Metafizyka. - Janeczek, Stanisław; Starościc, Anna (Dydaktyka filozofii, 2017)
This companion to metaphysics, a major branch of philosophy, provides a survey of the central problems of metaphysics and includes articles by many of the most distinguished Polish scholars in the field. Part one discusses ways in which the concerns of metaphysics has changed and expanded over time, as well as some recent theories. In addition, it contains some reflections on teaching metaphysics. The contributors to part two focuses on a broad selection of problems considered in the field of metaphysics and some recent theories of nature combined with a discourse on the methodological status of metaphysics. It is a useful resource for both students and academics.